HAMBATAN DALAM PROSES INTERNALISASI NORMA GLOBAL KESETARAAN GENDER PASCA RATIFIKASI CEDAW DI GHANA - Dewi, Kadek Purnama; Wiranata, I Made Anom; Nugraha, A.A Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
This research aims to understand the causes of the inhibition of the process internalization of global gender equality norm in Ghana after the ratification of CEDAW in 1986 by using a qualitative method that analyzes phenomena with theory. Ghana is one of the countries that ratified CEDAW in 1986. With that, Ghana has the responsibility to implement the values ??embodied in CEDAW. However, in reality, the process of diffusion of global norms is hampered. This obstacle is caused by several factors, namely: the delay in the process of institutionalizing the global norm of gender equality in Ghanaian society, the limited space for women in all walks of life in Ghana, and the perpetuation of the patriarchal culture in Ghana. In addition, to support the continued occurrence of women's discrimination in Ghana, the supporter of the conceptual framework, namely Galtung's Triangle of Violence (1990) is used to support women's discrimination. Keywords: Gender Equality, Internalization of Norms, Partiarchy, Triangle of Violence.